Pasture access and adaptive capacity in reindeer herding districts in Nordland, Northern Norway. Issue 1 (2nd January 2016) - Risvoll, Camilla; Hovelsrud, Grete Kaare
Abstract: Resource access and livelihood flexibility have been identified in the literature as two critical determinants of adaptive capacity. This paper shows that these aspects play important roles in reindeer herding in Nordland County, Norway, in terms of resilience to changes in social-ecological systems. Throughout history, reindeer herders have been able to draw on a broad range of adaptation options, but increased pasture fragmentation and loss of grazing land increasingly affect herders' adaptability to weather variability and climate change impacts. Our analysis of empirical material from three adjacent reindeer herding districts illustrates the linkages between socio-economic and environmental exposure sensitivities, how the herders adapt by exploring patterns of differential adaptive capacity, and how adaptive capacity is impacted. Two socio-economic (pasture encroachment and insufficient human resources) and two environmental (locked pastures and predation) exposure sensitivities emerged as the most prominent affecting pasture access, which was the most critical factor for ensuring the adaptive capacity of reindeer herders. Flexibility to alternate between adaptation strategies was another important characteristic. Adapting to these exposure sensitivities engenders benefits and unintended negative consequences for the herders. The key components to adaptive capacity identified in this paper provide an evidence-based focus for management action by those seeking to improve resilience of socio-ecological systems at the community level.